Toward a Theology of Mental Illness - Webb, Marcia (Journal of religion, disability & health, 2012)
This article considers research describing religious attitudes toward mental illness, including assumptions that mental illness may be evidence of personal sin or demonic influence. These assumptions are critiqued based upon a review of relevant Scriptural passages. A reformulation of theological conceptions of mental illness is then proposed, focusing on the following themes: heroism in frailty, freedom in finitude, complexity in disorder, and the stranger in our midst. In conclusion, the article offers potential implications of theologies describing a passable God for an understanding of human suffering in general, and the suffering in mental disorder in particular.